Evaluating Sleeper Bus Service Attributes on the Malang–Jakarta Route Using the Kano Model - Agitha, Soraya Ayu; Wicaksono, Ahcmad; Fauzul Rizal Sutikno (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2026)
The increasing demand for comfort-oriented long-distance transportation requires service providers to prioritize attributes that genuinely influence passenger satisfaction. This study evaluates the attributes of sleeper bus service on the Malang–Jakarta route using the Kano Model to identify those that drive satisfaction and dissatisfaction in asymmetric ways. Based on survey data from sleeper bus passengers, twelve service attributes were analyzed through paired functional and dysfunctional questions. The results indicate that most attributes fall into the Attractive and One-Dimensional categories, suggesting strong potential to enhance satisfaction when optimally delivered. WiFi availability, charging ports, and personal entertainment systems emerged as the strongest drivers of satisfaction, while the absence of onboard toilets and personal security features generated the highest dissatisfaction. The study contributes to transportation service quality literature by extending Kano-based analysis to the under-researched context of intercity sleeper buses in Indonesia. It provides actionable guidance for operators to prioritize investments that maximize customer experience and competitive differentiation.